Off-Road Adventures: Reading Statistics in Alexander von Humboldt’s Political Essay on the Kingdom of New Spain - Kutzinski, Vera M. (HiN - Alexander von Humboldt im Netz. Internationale Zeitschrift für Humboldt-Studien, 2024)
Abstract This article focuses on the visual qualities of Alexander von Humboldt’s statistical tables in his Political Essay on the Kingdom of New Spain (1808–1811, 2nd ed. 1825–1827) with special attention to how such composites of numbers, alphabetical script, and semiotic elements relate to narrative writing. I argue that Humboldt’s tables/tableaus open up spaces inside his narrative that fragment the reading process, inviting new conversations, connections, and ideas. Resumen Este articulo entretiene con los atributos visuales de las abundantes tablas estadísticas incluyendo en el Essai politique sur le royaume de la Nouvelle Espagne (1808–1811, 2nd ed. 1825–1827) de Alexander de Humboldt, en especial con las relaciones entre las combinaciones de números, escritura y elementos semióticos (que Humboldt llama “tableaux”) y la propia narrativa. Obran estas relaciones una fragmentación del proceso de leer, abriendo dimensiones y espacios en que se podrían manifestar nuevas conexiones, conversaciones e ideas innovadoras. Zusammenfassung Dieser Artikel befasst sich mit den bildhaften Eigenschaften der vielen statistischen Tabellen in Alexander von Humboldts Essai politique sur le royaume de la Nouvelle Espagne (1808–1811, 2nd ed. 1820–1827), wobei meine besondere Aufmerksamkeit den Verhältnissen gilt, die diese aus Zahlen, alphabetischer Schrift und semiotischen Elementen zusammengesetzten Komposita (die Humboldt als Tableaux bezeichnet) mit der beschreibenden Erzählung selbst eingehen: In diesen Verhältnissen offenbaren sich nämlich Dimensionen oder Räumlichkeiten, die durch die visuelle Zerteilung des Textes stets weitere, neue Verbindungen, Gespräche und Ideen zu produzieren suchen.